Successful catheter directed thrombolysis in postpartum deep venous thrombosis complicated by nicoumalone-induced skin necrosis and failure in retrieval of inferior vena caval filter. (25th July 2013) - Srinivas, B C; Patra, Soumya; Agrawal, Navin; Manjunath, C N
Abstract : Venous thromboembolism is an important cause for maternal morbidity and mortality in postpartum period. Though catheter-directed thrombolysis (CDT) is now considered as a safe and effective therapy for the management of deep venous thrombosis (DVT) but still it is not indicated in postpartum DVT. We are presenting a case of 22-year-old female patient who presented with post-partum lower limb DVT and managed successfully with CDT by using injection streptokinase and temporary inferior vena caval filter was inserted as prophylactic for pulmonary embolism as she had extensive DVT extending into inferior vena cava (IVC). During follow-up, she developed large skin necrosis in left lower limb which was managed by adding injection low-molecular-weight heparin. IVC filter also could not be retrieved even after trying all manoeuvres during follow-up after 2 weeks.